Predictors of refusal of provider initiated HIV testing among clients visiting adult outpatient departments in Jimma town, Oromia Region, Ethiopia: unmatched case control study - Lemu YK (Dove Medical Press, 2012)
Yohannes Kebede Lemu, Zewdie Birhanu Koricha, Lakew Abebe Gebretsadik, Ameyu Godesso RoroDepartment of Health Education and Behavioral Sciences, Jimma University, Jimma, EthiopiaBackground: Currently, provider-initiated human immunodeficiency virus (HIV) testing (PIHT) in health facilities is one of the strategies to advance HIV testing and related services. However, many HIV infected clients are missing the opportunities. This study intends to identify predictors of refusal of PIHT among clients visiting adult outpatient departments (OPDs) in Jimma town.Methods: An unmatched case control study was conducted among 296 clients: 149 cases refusing HIV testing and 147 controls accepting HIV testing. The study recruited clients from OPDs of four public health facilities between March 6 and April 8, 2011 using consecutive sampling. The study instrument was adapted mainly considering health belief model (HBM). Jimma University ethical committee reviewed the study protocol. Data were collected by face-to-face interview and analyzed using SPSS Statistics (IBM Corporation, Somers, NY) software, version 16.0. Data were subjected to factor and reliability analysis. For prediction analysis, the study used logistic regression and odds ratio (OR) with 95% confidence interval (CI). To see the effects among HBM constructs, the study used standardized beta (β) coefficients at P < 0.05.Results: The study findings showed adjusted protective effects on refusal of PIHT for residence outside study town [adjusted OR (AOR) (95% CI) = 0.41 (0.22–0.79)] and higher scores of perceived benefit of early testing [AOR (95% CI)] = 0.86 (0.69–0.99)], self efficacy to live with HIV [AOR (95% CI) = 0.79 (0.66–0.93)], nondisclosure agreement [AOR (95% CI) = 0.74 (0.58–0.93)], perceived explicitness of opt-out right during initiation [AOR (95% CI) = 0.74 (0.56–0.98)] and clients’ perceptions of selective initiation of HIV suspected [AOR (95% CI) = 0.54 (0.41–0.73)]. On the other hand, report of recent testing [AOR (95% CI) = 3.82 (1.71–8.55)] and perceived unpreparedness for testing [AOR (95% CI) = 1.86 (1.57–2.21)] aggravated refusal of PIHT. Exposure to cues to testing significantly reduced perceived barriers [β (P) = –0.05 (0.037)].Conclusion: Clients’ perceived barriers: feeling of unpreparedness for testing strongly aggravated refusal of test. Enhanced self-efficacy to live with HIV and presence of cues to HIV testing would reduce unpreparedness and protect from refusing PIHT.Keywords: HIV testing, provider-initiated, acceptance